(untitled) (Islamic Sciences Journal, 2023)
This paper summarizes a part of the explanatory narratives that clarified the Qur’anic verses in Surat Al-Waqi’ah selected from the book of Al-Hafiz Abi Naim Al-Asbahani, which tackles the hadiths mentioned in the description of Paradise, its creation, its location, its opening, its expansion. So they were collected and studied , including what was described in the description of the women of Paradise, beginning with the definition of Al-Hafiz Abu Naim and his book “The Character of Paradise”, studying the Qur’anic verses and mixing them with the explanations of the Sunnah. Studying the narrations in detail in terms of graduation and studying the men of the chain of transmission, as well as clarifying strange words and predicate gentleness are included. The researcher asks Almighty God that He guides me to what He loves and is pleased with.